An Exposition of Constructivism Account to Construct Knowledge and to Create Meaningful Learning Environment for Teacher Education - Rahman, Fadzilah Abd; Jalil, Habibah Abd; Hassan, Aminuddin (EDUCARE, 2008)
ABSTRACT: Since last ten years, it becomes indispensable to talk about constructivism in relation to the teaching and learning process. Yet the term of constructivism is still not well defined and contradicts. Generally constructivism refers to a set of views about how individuals learn and about how those who help them to learn ought to facilitate, which in this paper referred as Constructivist Learning Account (CLA). CLA holds an assumption that learners actively construct their own sets of meanings and understandings; knowledge is not a mere copy of the external world, nor is knowledge acquired by passive absorption or by simple transference from one person (educator) to another (a learner or knower). Clearly, knowledge is constructed not acquired. CLA also stresses that we cannot be certain that any two individuals will construct the same understandings. Even if they use the same linguistic formulations to express what they have learned, their deep understandings might be quite different. Hence, a better understanding of constructive learning accounts as a component of a long life learning process and how teacher education programme should engage with it is needed to create a meaningful learning environment.KEY WORDS: Constructivist Learning Account, knowledge is constructed, and meaningful learning.Â Â Â Â About the Authors: Dr. Fadzilah Abd Rahman, Dr. Habibah Abd Jalil, and Dr. Aminuddin Hassan are lecturers at the Faculty of Educational Studies, Universiti Putra Malaysia (UPM), 43400 Serdang, Malaysia. One of them could be reached at: fadzilah@educ.upm.edu.myHow to cite this article? Rahman, Fadzilah Abd, Habibah Abd Jalil & Aminuddin Hassan. (2008). âAn Exposition of Constructivism Account to Construct Knowledge and to Create Meaningful Learning Environment for Teacher Educationâ in EDUCARE: International Journal for Educational Studies, Vol.1(1) August, pp.17-30. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 17, 2008); Revised (July 17, 2008); and Published (August 17, 2008).